Frequency of healthy eating habits among students of a public university in Northeastern Brazil - Natanael de Jesus Silva; Adelson Alves de Oliveira-Júnior; Oscar Felipe Falcão Raposo; Danielle Góes da Silva; Raquel Simões Mendes-Netto; Kiriaque Barra Ferreira Barbosa (Universidade de Fortaleza, 2016)
Objective: The aim of this study was to measure the frequency of healthy eating habits among students of a public university in Northeastern Brazil. Methods: This is a cross-sectional population-based study. The sample was randomly composed of 933 undergraduate students of both genders aged 18-35 years. The frequency of healthy eating habits was assessed based on the adherence to the 10 Steps to Healthy Eating proposed by Brazil's Ministry of Health. The frequency of each step was measured through questions compiled from previous publications. Results: The steps to the healthy eating with the lowest frequencies of adherence were related to the practice of adding salt to prepared foods (18.6%, n=185) and to the consumption of fruits and vegetables (28.3%, n=281) and foods rich in fat (21.5%, n=213) and sugar (48.9%, n=486). However, there was an adequate consumption of beans (83.8%, n=832) and a prevalence of normal nutritional status of 69.6% (n=691) among the students. None of the interviewees followed all the steps to the healthy eating. The average adherence rate was at least 6 steps. Men and women presented different habits and food preferences. Conclusion: The university students presented a low frequency of healthy eating habits due to the high intake of food high in fat and sugar and mainly the low consumption of fruits and vegetables and the practice of adding salt to prepared foods. This may, in turn, predispose them to increased risks of morbidity and mortality from noncommunicable diseases.